Wave propagation and reflection in the aorta and implications of the aortic Windkessel - John V. Tyberg (Open Exploration Publishing Inc., 2021)
Some have said that it is inappropriate and perhaps impossible to consider wave and Windkessel phenomena simultaneously. For 50 years, arterial hemodynamics has been dominated by the frequency-domain "impedance analysis" in which it was assumed that all variations in aortic pressure and flow were caused only by forward- and backward-going waves. This paper is a review of the results of incorporating the effects of Frank's Windkessel. We have taken the view that measured aortic pressure is the sum of a Windkessel component and forward-going and backward-going wave components. When the Windkessel component is initially subtracted out, the pattern of propagation and reflection of wave components becomes clear. Furthermore, this analysis obviates the implications of impedance analysis that have not been explained satisfactorily.